(untitled) (BSAA arte, 2025)
The interest in spectacle and theatricality in the Baroque period encouraged the spread of machinery and mobile structures during the Corpus Christi festivities to replace the traditional processional frames. They became technically complex, rich and sumptuous in order to enhance the aesthetic value of the silver monstrance and also participated in an allegorical message at the service of the Eucharistic exaltation. This is the case of the triumphal chariot in the cathedral of Ávila, a piece still in use today that combines functionality and symbolism. The unpublished documentation allows us to situate the process of making it in Valladolid, to know the artists, the promoters and the costs, among other data.